Environmental responsibility at the University in human formation - Manéia, Arismar (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
The University has always sought to cultivate and to transmit knowledge, fundamental role to society, translated into development and intellectual progress. Today, higher education has a more universal and, in addition, more than technical vocational training and qualified, she should prepare the student for the full exercise of citizenship, caring for his research activity aimed at, too, the answer to the problems and the search for solution to the needs of the community. The mission of the University has to be expanded beyond the simple technical training that meets the practical purposes. The current environmental situation requires that the University plays a new role, assuming a critical-reflexive position with the goal of shaping a new rationality to the transformation of the traditional scientific models, promoting new knowledge and integrating the different knowledge. So, we need a review of environmental values in discussion within the University. It is, then, to the University have their social role faced with a more practical engagement on environmental issues, especially in the training of professionals and able to think about the environmental problems that plague humanity.